Ploeg, Ghislaine E. Van Der (2018), The Impact of the Roman Empire on the Cult of Asclepius. Impact of Empire XXX. Leiden: Brillon the Cult of Asclepius - Panagiotidou, Olympia (ARYS. Antigüedad: Religiones y Sociedades, 2019)
–